Tourism innovation technology, sustainability and creativity - Ratten, Vanessa; Braga, Vitor; Álvarez-García, José; Río Rama, Maria de la Cruz del 1969- (Routledge, 2020)
"Tourism can take many different forms and types but increasingly it is viewed as one of the most innovative industries. This book showcases the innovations in tourism through a creativity, sustainability and technology perspective. Tourism Innovation: Technology, Sustainability and Creativity addresses the growing use and importance of tourism innovation in society. Readers of this book will gain a global perspective on how the tourism industry is changing and taking advantage of emerging technologies, which will help them to foresee potential changes in the industry and plan for the future. Tourism innovation is defined as innovating in a cost-efficient manner by taking into account the available resources. Most of the focus on tourism innovation has been on developing countries but it is also used by companies in other locations. This book explores the way in which tourism innovation differs from other types of innovation and offers a creative solution to issues about sustainability and the circular economy. In this vein, it includes chapters addressing issues related to the following but not limited subjects: co-creation in innovation, social issues in innovation, leadership and innovation, forms of innovation, government innovation and innovation research. This book is suitable for tourism industry professionals, researchers and policy experts who are interested in how innovation is embedded in the tourism industry"--
Description based on print version record
Keywords: Tourism / Social aspects; Tourism / Information technology; Sustainable tourism